The Transition of Women's Ideology in Modern Javanese Literature - Yusro Edy Nugroho (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
AbstractThis study aims to analyze the struggle for women's idealism in modern Javanese literature. The approach used is ideological hegemony and content analysis methods to classify and analyze data from one classical Javanese literary work and two modern Javanese literary works, namely